From Scroll to Struggle: TikTok Usage and Its Influence on Attention Span and Academic Focus Among Youth in Malaysia - Daisy Mui Hung Kee; Jocelyn Ching Qiang Tai; Irene Shu Qian Ng; Yinyin Jia; Kaaviyamalar Parameswaran (AIBPM Publisher, 2025)
The rapid rise of TikTok as a dominant social media platform has raised concerns regarding its influence on youth cognitive functioning and academic performance. This study investigates how patterns of TikTok usage, including frequency of use, usage timing, and habitual or impulsive engagement, affect sleep quality, attention span, and academic performance among Malaysian youth. A quantitative research design was applied, and data were collected through an online survey involving 185 TikTok users aged between 15 and 30 years, followed by correlation and multiple regression analyses. Findings show that habitual or impulsive engagement produced the strongest negative effects, significantly reducing sleep quality (? = 0.296), attention span (? = 0.255), and academic performance (? = 0.296). Usage timing was also found to significantly impair sleep quality (? = 0.440), especially when participants engaged with TikTok late at night. Further, sleep quality (? = 0.155) and attention span (? = 0.426) positively predicted academic performance, with the overall model explaining more than 60 percent of the variance in the key outcome variables. The study concludes that unregulated and impulsive TikTok use undermines cognitive endurance and academic engagement, suggesting the need for digital literacy education, sleep hygiene awareness, and self regulation strategies to promote healthier and more balanced social media usage among youth.